Impact of reducing intake of red and processed meat on colorectal cancer incidence in Germany 2020 to 2050 - a simulation study - Niedermaier, Tobias; Gredner, Thomas; Hoffmeister, Michael; Mons, Ute; Brenner, Hermann (Nutrients, 2023)
Background: According to the International Agency for Research on Cancer (IARC), there is sufficient evidence for the carcinogenicity of processed meat consumption in humans, specifically regarding colorectal cancer (CRC) risk. Evidence for the carcinogenicity of red meat consumption is more limited but points in the same direction. Methods: A macro-simulation approach was used to calculate age- and sex-specific potential impact fractions in a 30-year period (2020-2050). Aims: We estimated numbers and proportions of future CRC cases preventable under different scenarios of reducing the intake of processed and red meat in the German population. Results: Eliminating processed meat intake could reduce the burden of CRC by approximately 205,000 cases in Germany (9.6%) in 2020-2050, 2/3 among males (145,000) and 1/3 among females (60,000). Without red meat intake, approximately 63,000 CRC cases could be avoided (2.9%), 39,000 among males and 24,000 among females. Reductions in the mean consumption of both processed and red meat by one or two servings (each 11 or 22 g) per day would be expected to reduce CRC case numbers by 68,000 (3.1%) and 140,000 (6.5%), respectively. Conclusion: A reduction in red and processed meat intake might substantially reduce the incidence of CRC in Germany. The means of achieving such a reduction might include price and taxation policies, food labeling, and clearer risk communication aiming to reduce individual intake.
Gesehen am 29.03.2023